Las compañías militares y de seguridad privada : ¿El comienzo del fin de los Estados?. (2018)
The aim of this paper is to problematize the main effects of the Private Military and Security Companies proliferation as a result of a neoliberal economic order in the external and internal spheres of States sovereignty. In this regard, a documental review with empirical and theoretical sources was used in order to understand this problematic. The first conclusion is that there exist a lack in the liberal economic philosophy concerning the treatment of security as a public service. Second, it was found that the effects of security privatization are more evident in countries where humanitarian and institutional weakness persists.